2007
DOI: 10.2460/ajvr.68.8.812
|View full text |Cite
|
Sign up to set email alerts
|

Mutant-prevention concentrations of enrofloxacin for Escherichia coli isolates from chickens

Abstract: For E coli infections of chickens, MPC appears to be useful for determining enrofloxacin-dosing strategies. The high MPC:MIC ratio may result in enrofloxacin-treatment failure in chickens infected with some wild-type gyrA E coli isolates despite the isolates' enrofloxacin susceptibility (MICs 0.125 to 1 microg/mL). For infections involving isolates with high MPCs, especially those containing mutations in gyrA and parC genes, treatment with combinations of antimicrobials should be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Bacteria growing in higher concentrations of enrofloxacin (0.1 mg ml À1 ) had more elongated cells and did not have mutations in gyrA, which has been shown to be the reason for decreased sensitivity of E. coli, including those exposed to low concentrations of fluoroquinolones. 39 Both inhibitors of the efflux pump, reserpine and CCCP, inhibited the growth of E. coli in the presence of enrofloxacin (data not shown), as has been shown previously for other fluoroquinolones. 32 However, in the media containing sterilized fecal extracts, no increase in sensitivity to enrofloxacin was observed in the presence of these pump inhibitors.…”
Section: Discussionsupporting
confidence: 76%
“…Bacteria growing in higher concentrations of enrofloxacin (0.1 mg ml À1 ) had more elongated cells and did not have mutations in gyrA, which has been shown to be the reason for decreased sensitivity of E. coli, including those exposed to low concentrations of fluoroquinolones. 39 Both inhibitors of the efflux pump, reserpine and CCCP, inhibited the growth of E. coli in the presence of enrofloxacin (data not shown), as has been shown previously for other fluoroquinolones. 32 However, in the media containing sterilized fecal extracts, no increase in sensitivity to enrofloxacin was observed in the presence of these pump inhibitors.…”
Section: Discussionsupporting
confidence: 76%
“…For most enrofloxacin-susceptible isolates, it is possible to achieve concentrations of enrofloxacin greater than their MPCs at the infection site. However, MPC values of mutant strains exceed the C max of enrofloxacin (1.88-2.44 µg/ml) in chickens [1,10,12]. APEC strains possessing at least 1 mutation in QRDRs account for 57.4% of APEC strains [16].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [12] reported that strains containing point mutations in the QRDR of gyrA with an MPC:MIC ratio of 16 showed higher mutation frequencies than did strains with MPC:MIC ratios of 2-4. Therefore, we examined the relationship between mutation frequency and MPC:MIC ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluoroquinolone MICs for Type I and II isolates were 8- to 16-fold higher than those of the wild type, and fluoroquinolone MPCs for Type I and II isolates were 32- to 256-fold higher than those of the wild type. A previous study suggested that wild-type strains had lower mutation frequencies compared with single-mutation strains [ 8 ].…”
mentioning
confidence: 99%